Rehabilitation of a Riparian Site Contaminated by Tailings from the Fundão Dam, Brazil, Using Different Remediation Strategies - Gomes, Alessandra R.; Antão, Arthur; Santos, Amanda G.P.; Lacerda, Tomás J.; Medeiros, Mirelli B.; Saenz, Luis Alberto I.; Alvarenga, Stael; Santos, Carlos Henrique [UNESP]; Rigobelo, Everlon C. [UNESP]; Scotti, Maria Rita (Oxford University Press (OUP), 2021)
The tailings spilled by the Fundão Dam rupture in the Doce River basin (Brazil) had a high pH, elevated sodium (Na) and ether amine, and low soil organic matter. With the aim of decreasing the toxic compounds, we established 2 remediation strategies: treatment 1, phytoremediation with tolerant native species of the Atlantic Forest cultivated on scraped sediment plus the incorporation of organic matter; and treatment 2, phytoremediation with native species plus superficial deposition of organic matter. The experimental site was compared with a degraded site that the dam tailings had reached and with a preserved site, a fragment of preserved Atlantic Forest. After 12 mo, plants showed an outstanding growth, especially after treatment 1 (~4 m), and the remediation procedures resulted in significant decreases in pH (from 8.0 to ~ 6.0), Na (from 154 to 22–35 mg/kg), electrical conductivity, and ether amine (from 6.0 to 0.5 mg/kg) in both treatments. By contrast, ammonium, a product of ether amine degradation, showed a significant increase in the experimental site, along with a significant increase in nitrate and improvement of soil microbial populations assessed by phospholipid fatty acid analysis. The treatments also improved soil fertility in the experimental site, as estimated by soil nutrients, cation exchange capacity, and soil aggregation. Based on the parameters analyzed, a principal component analysis showed that samples from the degraded site and the preserved site clustered in an opposite position and those from the experimental site clustered in an intermediate position but closer to the samples from the preserved site. Overall, our results demonstrated that the remediation procedures adopted were effective and resulted in rehabilitation of a riparian forest contaminated with dam tailings that included Na and ether amine. Environ Toxicol Chem 2021;40:2359–2373. © 2021 SETAC.
Keywords: Ether amine; Mariana; pH; Phytoremediation; Reclamation; Samarco; Sodium